2021
DOI: 10.1111/obr.13385
|View full text |Cite
|
Sign up to set email alerts
|

The built environment as determinant of childhood obesity: A systematic literature review

Abstract: Summary We evaluated the epidemiological evidence on the built environment and its link to childhood obesity, focusing on environmental factors such as traffic noise and air pollution, as well as physical factors potentially driving obesity‐related behaviors, such as neighborhood walkability and availability and accessibility of parks and playgrounds. Eligible studies were (i) conducted on human children below the age of 18 years, (ii) focused on body size measurements in childhood, (iii) examined at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…According to current evidence, a child-friendly built environment has high walkability levels (e.g., well-connected streets) and provides access to recreational facilities (e.g., parks and playgrounds), that have been positively associated with physical activity (PA), including active commuting to/from school (ACS) and recreational play [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Furthermore, a positive built environment has a significant role in preventing non-communicable diseases reducing obesity rates, diabetes or coronary heart disease [ 1 , 4 , 12 ]. Although the causes of obesity are multifactorial, built environmental factors can potentially drive obesity-related behaviors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to current evidence, a child-friendly built environment has high walkability levels (e.g., well-connected streets) and provides access to recreational facilities (e.g., parks and playgrounds), that have been positively associated with physical activity (PA), including active commuting to/from school (ACS) and recreational play [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Furthermore, a positive built environment has a significant role in preventing non-communicable diseases reducing obesity rates, diabetes or coronary heart disease [ 1 , 4 , 12 ]. Although the causes of obesity are multifactorial, built environmental factors can potentially drive obesity-related behaviors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a positive built environment has a significant role in preventing non-communicable diseases reducing obesity rates, diabetes or coronary heart disease [ 1 , 4 , 12 ]. Although the causes of obesity are multifactorial, built environmental factors can potentially drive obesity-related behaviors [ 12 ]. The neighborhood built environment has significantly links to children’s behaviors, such as PA and sedentary lifestyles [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's society is increasingly obesogenic with food environments [29] and the built environment [30] being associated with childhood obesity. A recent study in Australia found that almost 75% of outdoor food advertisements within 500 m of primary and secondary schools promoted unhealthy foods and beverages [31].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is limited evidence on the association between perceived urban environment attributes and obesity indices 9,17,18 . Epidemiologic studies 17 and systematic reviews [19][20][21] indicate that the findings of these associations are varied. Although some of the apparent discrepancies could be due to diversity of procedures engaged, the main issue that may clarify this variety in results is the limited variability.…”
mentioning
confidence: 99%